An unusual presentation of perinatally transmitted hepatitis C. Issue 2 (1st February 2003) - Mohan, P; Chandra, R S; Kleiner, D E; Luban, N L C
Abstract : A unique presentation of perinatally acquired hepatitis C (HCV) with acute jaundice and chronic aggressive liver disease in a previously asymptomatic preadolescent is described. The difficulties in establishing the diagnosis and the importance of confirmatory testing for HCV in cryptogenic liver disease are discussed.